Contact sensitizers downregulate the expression of the chemokine receptors CCR6 and CXCR4 in a skin dendritic cell line - Cruz, MT (2010)
Chemokines are involved in the control of dendritic cell (DC) trafficking, which is critical for the immune response, namely in allergic contact dermatitis (ACD). In this work, we investigated by flow cytometry the effect of the contact sensitizers 2,4-dinitrofluorobenzene (DNFB), 1,4-phenylenediamine (PPD) and nickel sulfate (NiSO(4)), on the surface expression of the chemokine receptors CCR6 and CXCR4 in DC. As an experimental model of a DC we used a fetal skin-derived dendritic cell line (FSDC), which has morphological, phenotypical and functional characteristics of skin DC. Our results show that all the skin sensitizers studied decreased the membrane expression of the chemokine receptors CCR6 and CXCR4. In contrast, 2,4-dichloronitrobenzene (DCNB), the inactive analogue of DNFB without contact sensitizing properties, was without effect on the surface expression of these receptors. Lipopolysaccharide (LPS), which induces the maturation of DC, also reduced surface CCR6 and CXCR4 expression.